Pengaruh Literasi Teknologi Dan Infrastruktur Teknologi Dalam Upaya Memaksimalkan Pendidikan Kewarganegaraan Digital (Studi Korelasi Pada SMA Negeri Di Kota Sukabumi) - Ginanjar, Denda; Sri Rahayu Pudjiastuti; Suidat (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2025)
The digital era demands educational transformation that integrates technological literacy and technological infrastructure to support digital citizenship education. This research aims to analyze the influence of technological literacy and technological infrastructure in maximizing digital citizenship education among high school students in Sukabumi City. The research method uses a quantitative approach with associative descriptive design. The research sample consisted of 309 students from State Senior High Schools in Sukabumi City selected through probability sampling techniques. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling (SEM) with SPSS AMOS. The results show that technological literacy has a significant positive effect on digital citizenship education with coefficient β = 0.530 (p < 0.001), indicating that increased technological literacy will improve digital citizenship understanding by 53%. Technological infrastructure also has a significant positive effect with coefficient β = 0.147, although its influence is smaller compared to technological literacy. Simultaneously, the combination of technological literacy and technological infrastructure explains 36% of the variation in digital citizenship education (R² = 0.360). The findings indicate that technological literacy is the main predictor of successful digital citizenship education, while technological infrastructure serves as a supporting facilitator. This research recommends a holistic approach in developing digital education policies that integrate improving students' technological literacy with strengthening school technological infrastructure to create responsible and ethical digital citizens.